Novel isatin-Schiff base Cu(II) and Ni(II) complexes. X-ray crystal structure of bis[3-(4-hexylphenylimino)-1H-indol-2(3H)-one]-dichlorocopper(II) complex - Ercag, A; Yildirim, SO; Akkurt, M; Ozgur, MU; Heinemann, FW (ELSEVIER SCIENCE INC, 2006)
Schiff base ligand (HL) derived from 4-hexylaniline with isatin (1H-indole-2,3-dione) and its complexes with Cu(II), Ni(II) were prepared and characterized by analytical, spectroscopic (IR, UV-Vis, Mass) techniques, electrical conductivity, magnetic and thermal measurements. The crystal and molecular structure of [Cu(HL)(2)Cl-2] was determined by a single-crystal X-ray diffraction study. The molecular structure of the title compound has an inversion center on the Cu atom.
Keywords: mononuclear Cu(II) and Ni(II) complexes; isatin-anilines; Schiff base; crystal structure; MANNICH-BASES; CONDUCTIVITY; Chemistry